Immunopathogenesis of Silicotuberculosis: A Literature Review - Indi Esha; Elvando Tunggul Mauliate Simatupang (Respiratory Science, 2023)
Silicotuberculosis is a tuberculosis infection that emerges as a silicosis complication. A silicosis patient is 2.8 to 39 times more likely to develop pulmonary tuberculosis (TB). Moreover, the fibrotic condition caused by silicosis may exacerbate the symptoms and worsen the clinical outcome of silicotuberculosis patients.  The current report suggests that the immune system plays an important role in the pathogenesis of this disease. Silicosis or silica exposure might interfere with the immunological response, especially the macrophages, which permit the Mycobacterium tuberculosis to infect the host. In this literature review, we will discuss the definition, epidemiology, and immunopathogenesis of silicotuberculosis.